The prevalance of Hepatitis B, C and HIV seropositivity among inpatient iv heroin users - Mırsal, Hasan; Kalyoncu, Ö. Ayhan; Pektaş, Özkan; Tan, Devran; Beyazyürek, Mansur (Journal of Dependence, 2003)
Objective: IV drug use is a risk factor for the spread of Hepatitis B-C and HIV infections. The aim of this study is to determine the rate of the seropositivity of those agents in an inpatient sample and to evaluate sociodemographic and clinical correlates related to this issue. Method: To study, 107 iv drug users who were recruited from totally 391 heroin dependent inpatients was done. All patients were diagnosed with heroin dependence according to DSM-IV criteria by two psychiatrists. Sociodemographic and clinical features was determined by a detailed questionnaire. Serologic tests were assessed by Microparticle Enzyme Immunoassay technique (Abbott). Frequency, chisquare and t-test statistics were done on data. Results: The sex ratio in the study group was 7.5 % (n=8) as female, 92.5 % (n=99) as male. The mean age of group was 28.9 years (±6.9); the mean length of time of iv heroin use was 1.9 years (±1.8). The rate of sharing injector was 48.6 % (n=53). The distribution of serologic test results were as follows; HbsAg 2.8% (n=3), Anti-HBs 29.9% (n=32), Anti-HCV 44.9% (n=48), Anti-HIV I-II 4.7 % (n=5). Conclusion: The rate of seropositivity with HBV, HCV, HIV is found higher than general population. For viral hepatitis and HIV infections are growing health problems in Turkey, educational and preventive interventions should be planned especially for high risk groups throughout the country.